INTERKALASI BENZALKONIUM KLORIDA KE DALAM MONTMORILLONIT TERAKTIVASI ASAM DAN PEMANFAATANNYA UNTUK MENINGKATKAN KUALITAS MINYAK DAUN CENGKEH - P. Suarya (Jurnal Kimia (Journal of Chemistry), 2009)
This research was conducted to observe the surfactant intercalation into acid-activated montmorillonite clay.This clay was applied as adsorbent for increasing the quality of clove leaf oil. The acid used as an activation was 1.5M sulphuric acid and the surfactant for intercalation was Benzalkonium Chloride (BKC) with concentration variation(0; 0.1; 0.5; 1; and 2%). The result of the reseach showed that the changes of basal spacing d001 for S0-0; Sa-0; Sa-0,1;Sa-0,5; Sa-1; and Sa-2 were 15.15548; 15.40269; 15.20580; 14.62099; 14.77594; and 14.74415 Å respectively. Thesurface area for S0-0; Sa-0; Sa-0,1; Sa-0,5; Sa-1; and Sa-2 were 26.2239; 27.4035; 26.0482; 26.4557; 27.7885; and 26.6809m2/g respectively. The Sa-0,1 adsorbent had the highest surface acidity (1.0135 ± 0.01100 mmol/g). Every gram ofadsorbent Sa-0,1 had the highest adsorption capacity to clarify 20.0 mL clove leaf oil at 120 minutes contact time.After adsorption by Sa-0,1 the clove leaf oil was clearer and contained higher concentration of eugenol than beforeadsorption.